Burnt fuel remains (Scottish Historical and Archaeological Internet Reports, 2001)
There are two types of probable fuel residue. One is a fused mixture of organic materials (from a range of contexts in Periods I, IV and V) and the other, less frequent, type is represented by fragments of probable burnt coal from midden deposits in Period IV-V.